2016
DOI: 10.21839/jaar.2016.v1i3.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leucaena forage and silage substitution in concentrates on digestibility, nitrogen utilization and milk yield in dairy cows

Abstract: This experiment was conducted to determine the effect of feeding leucaena forage and silage substitution in concentrate on the performances of dairy cows. Nine cross-bred Holstein Friesian cows (410±12kg) in the 12th week of lactation were randomly allocated to one of three treatment groups with three replicates/treatments in a completely randomized design. The three treatments were control diet without substitution of leucaena forage and silage (DLFS0), diet with substitution of leucaena forage 10% (DLF10) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Thus, the concentrates have been supplemented to roughage diets to obtain the highest performances of animals. Groundnut cake, sesame cake, cotton seed cake, broken rice, rice bran and chickpea mill are used as concentrate sources for ruminants in Myanmar MyoKhaing et al, 2016). Supplementation of concentrates to roughage based diet enhances the animal performances, however the feed cost are high because of expensiveness of concentrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the concentrates have been supplemented to roughage diets to obtain the highest performances of animals. Groundnut cake, sesame cake, cotton seed cake, broken rice, rice bran and chickpea mill are used as concentrate sources for ruminants in Myanmar MyoKhaing et al, 2016). Supplementation of concentrates to roughage based diet enhances the animal performances, however the feed cost are high because of expensiveness of concentrates.…”
Section: Introductionmentioning
confidence: 99%
“…Norton (1994) also reported that the potential roles of tree forages in ruminant nutrition are palatable, high quality protein content, high digestibility, as source of by-pass protein, vitamin, and minerals, and can be utilized for the partial replacement of commercial concentrates to give less cost of feeding. Moreover, gliricidia and leucaena leaves could be used as nitrogen sources without causing detrimental effects in ruminants (Lwin Naing Oo, 2002;MyoKhaing et al, 2016). However, the supplementation of high quality legume forage to exotic grass on feed cost and animal performances are still remaining to investigate.…”
Section: Introductionmentioning
confidence: 99%